2016
DOI: 10.1007/s00423-016-1527-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled clinical trial assessing the effects of oral nutritional supplements in postoperative gastric cancer patients

Abstract: This study showed ONS after total gastrectomy to significantly diminish postoperative weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 22 publications
4
47
0
2
Order By: Relevance
“…Clarifying the mechanisms of sarcopenia in patients with cancer may help reveal the mechanism of cachexia, the root of cancer death. Previous studies have shown that various methods of nutritional support are effective for improving dietary intake and outcomes in patients who lose weight after surgery (21,22). Hatao et al found that the use of oral nutritional supplements after total gastrectomy significantly diminished postoperative weight loss (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarifying the mechanisms of sarcopenia in patients with cancer may help reveal the mechanism of cachexia, the root of cancer death. Previous studies have shown that various methods of nutritional support are effective for improving dietary intake and outcomes in patients who lose weight after surgery (21,22). Hatao et al found that the use of oral nutritional supplements after total gastrectomy significantly diminished postoperative weight loss (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that various methods of nutritional support are effective for improving dietary intake and outcomes in patients who lose weight after surgery (21,22). Hatao et al found that the use of oral nutritional supplements after total gastrectomy significantly diminished postoperative weight loss (21). If oral nutritional supplements can be demonstrated to also be efficacious for preventing postoperative muscle mass reduction, such oral nutritional supplements could consequently be administered to patients with sarcopenia, which is an especially common finding after total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Hatao et al investigated the effects of ONS on postoperative body weight loss in patients with gastric cancer who had undergone total gastrectomy or distal gastrectomy (24). In their study, although weight loss in the ONS group after total gastrectomy was significantly less than that in the control group, the weight loss and skeletal muscle mass loss after distal gastrectomy did not significantly differ between the groups.…”
Section: Gradementioning
confidence: 99%
“…To our knowledge, malnutrition is a common presentation in GA patients due to cancer cachexia and the obstruction of gastrointestinal tract. For the surgical patients, the increased physical metabolism and insufficient calorie intake further deteriorate the metabolism balance, which causes minor (fatigue or delayed recovery) or major adverse effects (complication or mortality) [50]. Therefore, preoperative screening is very imperative to recognize the malnourished patients, who need nutrition intervention program [51].…”
Section: Discussionmentioning
confidence: 99%